Mid-to Late Holocene climatic and anthropogenic influences in Mpondoland, South Africa. (1st June 2021) - Hahn, Annette; Neumann, Frank H.; Miller, Charlotte; Finch, Jemma; Frankland, Tarryn; Cawthra, Hayley C.; Schefuß, Enno; Zabel, Matthias
Abstract: Mpondoland on the South African east coast is a particularly dynamic region in terms of climate change as it is influenced by both temperate and tropical circulation and climate systems. We present a sediment record that indicates regional climatic change and anthropogenic influence during the last ∼5500 yr. Catchment data allow an understanding of signal transmission from the catchment to the site of the marine core. Plant-wax isotope distributions and elemental composition, as well as palynological, burned phytolith and micro-charcoal data, are used to infer paleoclimatic shifts and reconstruct past human activity. Whereas previous studies have often disregarded early anthropogenic drivers of environmental change, our study provides palynological evidence of human impacts and geochemical evidence of increased erosion starting as early as ∼1500 years ago. Downcore proxy analysis suggests that particularly humid conditions persisted from ∼900 to ∼300 cal yr BP, encompassing both the Medieval Climate Anomaly and the Little Ice Age. We suggest that humidity during the Medieval Climate Anomaly was sourced from a poleward shift of the Southern Hemispheric Westerlies and the South African high-pressure cell, allowing for the southward expansion of the Southern Indian Ocean Convergence Zone. During the Little Ice Age, the equatorward movement of the Southern Hemispheric Westerlies probably brought increased rainfall to areas that are normally beyond the northern limit of the Southern Hemispheric Westerlies. Comparison of our record to available regional archives of centennial-scale late Holocene climate variability in South Africa demonstrates that Mpondoland is located at a transition zone of tropical and sub-tropical climatic influences. Highlights: Anthropogenic drivers of environmental change as early as ∼1500 years ago. A southward expansion of the Southern Indian Ocean Convergence Zone caused a wet Medieval Climate Anomaly in Mpondoland. A Southern Hemispheric Westerlies equatorward shift brought increased rainfall to Mpondoland during the Little Ice Age.